Bitcoin awareness and usage in Canada - Christopher S. Henry; Kim P. Huynh; Gradon Nicholls (Bank of Canada, 2017)
There has been tremendous discussion of Bitcoin, digital currencies and FinTech. However, there is limited empirical evidence of Bitcoin's adoption and usage. We propose a methodology to collect a nationally representative sample using the Bitcoin Omnibus Survey (BTCOS) to track the ubiquity and usage of Bitcoin in Canada. We find that about 64 percent of Canadians have heard of Bitcoin, but only 2.9 percent own it. We also find that awareness of Bitcoin is strongly associated with men and those with college or university education: additionally, Bitcoin awareness is more concentrated among unemployed individuals. On the other hand, Bitcoin ownership is associated with younger age groups and a high-school education. Furthermore, we construct a test of Bitcoin characteristics to gauge the level of knowledge held by respondents who were aware of Bitcoin, including actual owners. We find that knowledge is positively correlated with Bitcoin adoption. We attempt to reconcile the difference in awareness and ownership by decomposing the transactional and store-of-value motives for holding Bitcoin. Finally, we conclude with some suggestions to improve future surveys on digital currency, in particular, to achieve precise estimates from the hard-to-reach population of digital currency users.
Keywords: E4; C12; 330; Bank notes; Digital currencies; Econometric and statistical methods